Serial protein misfolding cyclic amplification (sPMCA) to detect surrogate markers for chronic wasting disease in surface water, municipal water and soil - Nichols, Tracy A., author; Zabel, Mark, advisor (Colorado State University. Libraries, 2008)
Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy of deer and elk. Research has indicated that CWD is transmitted horizontally, and that both blood and saliva can transmit disease. Environmental exposure to pens where infected animals have been kept has resulted in disease transmission to deer. However, examination of environmental components such as soil and water for prions has been hampered by sensitivity limitations of conventional western blotting and inoculation limitations of bioassays. In this study we evaluated the ability of protein misfolding cyclic amplification (PMCA) to detect protease-resistant prion protein (PrPres) in environmental samples such as water and soil. Serial protein misfolding cyclic amplification (sPMCA) of PrPres, the misfolded proteinase-resistant protein associated with prion disease, was used to detect prion-infected brain homogenate spiked into soil and water to determine detection limits of this assay in environmental samples. The PrPres detection limit for water after 6 rounds of PMCA was 1:26 x 106. Detection of a CWD spike in soil with our current methodology was not possible. We next evaluated surface and drinking water from a CWD endemic region of Colorado for PrPres by sPMCA. PrPres was detected in Cache la Poudre River and flocculant samples at a time of high snowmelt runoff, suggesting that sPMCA can be a useful tool in evaluating water for PrP res in CWD-endemic areas.
Keywords: chronic wasting disease; environmental contamination; prions; serial protein misfolding cyclic amplification; soil; surrogate markers; transmission; water; molecular biology; microbiology; animal sciences; animal diseases